The influence of marketing mix and service quality of Puskesmas Bojong Nangka against BPJS patient satisfaction - Rahmi, Novi Henriyati; Sampurno, Sampurno; Sumaryono, Wahono (Universitas Muhammadiyah Malang, 2022)
This study aims to analyze how the influence of the service marketing mix in this product, price, promotion, location, people, physical evidence, and the process, and the quality of health services in this case direct evidence (tangibles), reliability, responsiveness, assurance, and empathy at the Puskesmas Bojong Nangka Gunung Putri District, Bogor Regency towards patient satisfaction BPJS. The research method used a cross-sectional or cross-sectional descriptive analysis method. The place of research was at the Puskesmas Bojong Nangka, Gunung Putri, Bogor. The research sample amounted to 100 people. Data collection techniques are questionnaires and observations. Analysis of research data is by the Multiple Linear Regression test with Y1 = 1.515 + 0.064X1 + 0.073X2. The study concludes that the marketing mix and the quality of health services affect the satisfaction of BPJS patients in partial and both. Puskesmas quality variables more influence BPJS patient satisfaction compared to service marketing mix variables.